Welfare Economics of Variable Tastes - Harsanyi, John C. (Review of Economic Studies, 1953)
Journal Article Welfare Economics of Variable Tastes Get access John C. Harsanyi John C. Harsanyi Brisbane, Australia Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Pages 204–213, https://doi.org/10.2307/2295773 Published: 01 January 1953